2017
DOI: 10.4172/2157-7145.1000379
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Time Duration of Life Stages of Chrysomya megacephala and Chrysomya rufifacies (Diptera: Calliphoridae) during Different Seasons

Abstract: Accurate estimation of post mortem interval (PMI) can be crucial to the successful investigation of suspicious death. The forensic indicator blowflies are essential for accuracy in estimation of PMI. The Calliphoridae species Chrysomya megacephala and Chrysomya rufifacies were reared in laboratory condition for studying their time duration of different stages under the fluctuating temperature in three different seasons (i.e. rainy season, winter season and summer season).In laboratory, at the fluctuating tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Since different succession patterns, geographic distributions, elevations, environmental temperature, and humidity (Siddiki & Zambare 2017) can affect the composition, development, and life cycle of insect fauna, the knowledge of local entomofauna of necrophagous insects is very important in order to introduce evidence into a forensic investigation. Many studies of forensic entomology have reported the entomofauna of India (Abd-Algalil & Zambare 2017;Bharamal 2016;Bharti & Sing 2017;Jadav & Sathe 2014;Sathe et al 2013), but there is a paucity of data on the entomofauna of central India (Nagpur).…”
Section: Introductionmentioning
confidence: 99%
“…Since different succession patterns, geographic distributions, elevations, environmental temperature, and humidity (Siddiki & Zambare 2017) can affect the composition, development, and life cycle of insect fauna, the knowledge of local entomofauna of necrophagous insects is very important in order to introduce evidence into a forensic investigation. Many studies of forensic entomology have reported the entomofauna of India (Abd-Algalil & Zambare 2017;Bharamal 2016;Bharti & Sing 2017;Jadav & Sathe 2014;Sathe et al 2013), but there is a paucity of data on the entomofauna of central India (Nagpur).…”
Section: Introductionmentioning
confidence: 99%
“…the dung beetle Onthophagus lecontei (Coleoptera: Scarabaeinae) (Arellano et al ., )], which is exposed to similar predation pressures but under different environmental conditions, as well as other necrophagous insects that colonize cadavers later in succession [i.e. oriental latrine flies such as Chrysomya megacephala (Diptera: Calliphoridae) (Siddiki and Zambare, ) and black soldier flies such as Hermetia illucens (Stratiomyidae) (Nguyen et al ., )]. Note that, for the black soldier fly, mean values of individuals reared on liver are listed.…”
Section: Introductionmentioning
confidence: 99%